2021
DOI: 10.3389/fimmu.2021.730088
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Effects of SARS-CoV-2 Linking Lung Infection to the Brain

Abstract: In December 2019, a new viral disease emerged and quickly spread all around the world. In March 2020, the COVID-19 outbreak was classified as a global pandemic and by June 2021, the number of infected people grew to over 170 million. Along with the patients’ mild-to-severe respiratory symptoms, reports on probable central nervous system (CNS) effects appeared shortly, raising concerns about the possible long-term detrimental effects on human cognition. It remains unresolved whether the neurological symptoms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 174 publications
(203 reference statements)
0
12
0
Order By: Relevance
“…A myriad of complex intricate factors alters smooth muscle tonus and vessel diameter in COVID‐19 patients. Direct hypoxaemia and cytokine release in the CNS after a systemic immune response can already lead to the loss of tonicity in larger vessels with thick smooth muscle layers [ 43 , 44 , 45 , 46 , 47 , 48 ]. Previous studies have shown that SARS‐CoV‐2 can directly infect the smooth muscle cells within the blood vessel wall in different organs including the brain, heart, liver, kidney and pancreas [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A myriad of complex intricate factors alters smooth muscle tonus and vessel diameter in COVID‐19 patients. Direct hypoxaemia and cytokine release in the CNS after a systemic immune response can already lead to the loss of tonicity in larger vessels with thick smooth muscle layers [ 43 , 44 , 45 , 46 , 47 , 48 ]. Previous studies have shown that SARS‐CoV‐2 can directly infect the smooth muscle cells within the blood vessel wall in different organs including the brain, heart, liver, kidney and pancreas [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As studies generally lack control patients with other severe illnesses, the specificity of such findings to SARS-CoV-2 also remains unclear. Systemic inflammatory processes, including cytokine release, have been linked to glial activation with expression of chemoattractants that recruit immune cells, leading to neuroinflammation and injury 85 . Cerebrospinal fluid concentrations of neurofilament light, a biomarker of neuronal damage, were reportedly elevated in patients hospitalized with COVID-19 regardless of whether they exhibited neurologic diseases 86 .…”
Section: Lonelinessmentioning
confidence: 99%
“…Systemic cytokines can also cause glial activation leading to increased CNS levels of chemoattractants for peripheral immune cells, promoting inflammation [74]. Studies of postmortem specimens from patients who succumbed to acute COVID-19 reveal hypoxic damage, microglial activation, astrogliosis, leukocytic infiltration, and microhemorrhages [29,75 ▪▪ ,76 ▪▪ ].…”
Section: Acute Severe Acute Respiratory Syndrome Coronavirus-2 Infect...mentioning
confidence: 99%